Vietnam's integration into the world business community for peace, development, mutual benefit, through the rule of law - Ngo, Ba Thanh (Vietnam, 1993)
Non recognition of a nation in the geopolitical position of Vietnam is a policy out of date. Economic problems are destined to produce tough U.S. negociations with certain Asian States, some of them allies.
Keywords: Quan hệ quốc tế,International relations; Việt Nam,Vietnam